Shelf life and carbohydrate metabolism of arracacha roots stored under refrigeration and PVC film - Ribeiro, Rosilene Antonio; Finger, Fernando Luiz; Puiatti, Mário; Casali, Vicente Wagner Dias (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the influence of the storage temperature and stretch polyvinylchloride (PVC) film on the loss of fresh weight and water, on the development of chilling injury symptoms, and on the postharvest metabolism of carbohydrates, in arracacha tuber roots (Arracacia xanthorrhiza). The PVC film reduced the fresh weight loss and kept water content in the roots during 60-day storage period at 5 and 10oC. PVC film in both storage temperatures inhibited the development of external and internal chilling injury symptoms. The low temperatures induced the increase of soluble sugar content and decrease of starch concentration, where the increase in soluble sugar was transient in roots stored without PVC film, and the rate of starch degradation was higher compared to the roots stored with PVC.